Bed expansion and particle classification in liquid fluidized beds with structured internals - Piovano, Stella Maris (2015)
The inclusion of a structured packing as internal in a liquid-solid fluidized bed allows expansion of the liquid velocity operation range before elutriation, promoting the liquid solid contact and mixing. The bed expansion of liquid-solid fluidized beds provided with structured packing as internals is examined, for solids denser than the liquid phase and within a wide range of operating conditions. A correlation to estimate the bed expansion in liquid-solid fluidized beds using structured packing as internals is developed. In addition, the feasibility of employing structured packing as internals for favoring classification of different density particles is demonstrated by analyzing the mass elutriated from the column at different liquid velocities for single particles or binary mixtures.